Endothelial glycocalyx in traumatic brain injury associated coagulopathy: potential mechanisms and impact - Zou, Zhimin (J Neuroinflammation, 2021)
Traumatic brain injury (TBI) remains one of the leading causes of death and disability worldwide; more than 10 million people are hospitalized for TBI every year around the globe. While the primary injury remains unavoidable and not accessible to treatment, the secondary injury which includes oxidative stress, inflammation, excitotoxicity, but also complicating coagulation abnormalities, is potentially avoidable and profoundly affects the therapeutic process and prognosis of TBI patients. The endothelial glycocalyx, the first line of defense against endothelial injury, plays a vital role in maintaining the delicate balance between blood coagulation and anticoagulation. However, this component is highly vulnerable to damage and also difficult to examine. Recent advances in analytical techniques have enabled biochemical, visual, and computational investigation of this vascular component. In this review, we summarize the current knowledge on (i) structure and function of the endothelial glycocalyx, (ii) its potential role in the development of TBI associated coagulopathy, and (iii) the options available at present for detecting and protecting the endothelial glycocalyx.